Fathers’ parenting styles in Chinese families in urban Malaysia - Hong, Chi Yee; Baharudin, Rozumah; Hossain, Ziarat (Universiti Putra Malaysia Press, 2012)
The primary objectives of this study were to examine: 1) fathers’ parenting styles, and 2) the relationships between selected variables within the family ecosystems (e.g., father’s age, education, work hours, income, and psychological distress, child’s age and sex, as well as family income, number of children in the family, and marital quality) and fathers’ parenting styles within the Chinese families in Malaysia. One hundred fathers, with children between the ages of 7 to 10 years from two-parent Chinese families residing in three urban cities in the state of Selangor in Malaysia, participated in the current study. Respondents completed a self-administered questionnaire which consisted of the following measures: Edwards Parenting Scale, Kessler Psychological Distress Scale – K10, Kansas Marital Satisfaction Scale, and a Demographic Sheet. Descriptive analyses reveal that the proportion of the respondents practicing authoritative (37.0%) parenting styles was the highest, and this was followed by authoritarian (34.0%) and permissive (29.0%). styles. Correlation analyses indicated that fathers’ level of psychological distress and the number of children in the family significantly and positively related to the authoritarian parenting style, whereas fathers’ level of education and report of marital quality significantly and positively related to authoritative parenting style, with the number of children being significantly and negatively related to the authoritative parenting style. Findings are interpreted in line with the Chinese cultural expectations for fathering behaviour.